Pengaruh Cash Turnover, Loan to Deposit Ratio, Capit al Adequacy Ratio, dan Dana Pihak Ketiga terhadap Profitabilitas LPD - Putu Cahyadi Sujana; I Ketut Mustanda (Faculty of Economics and Business Udayana University, 2014)
The purpose of this study was to determine the effect of cash turnover , loan to deposit ratio, capi tal adequacyrat io, and third-party funds to the profi tabil ity of Lembaga Perkreditan Desa (LPD) in Denpasar 2010-2012.Thi s study used observasion method is to study and look at the financial statements of the LPD period 2010-2012 and found a sample of 34 LPD. This study found that the cash turnover , loan to deposit ratio and capi taladequacy rat io by part ial signi ficant positive effect on the profitability of LPD in Denpasar 2010-2012.Meanwhile, third-party funds significant negat ive effect on the profitabili ty of LPD in Denpasar 2010-2012.